2019
DOI: 10.1158/0008-5472.can-18-2414
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pyruvate Dehydrogenase Kinase Enhances the Antitumor Efficacy of Oncolytic Reovirus

Abstract: NAC Lactate Metabolic reprogramming enhances the susceptibility of cancer cells to the antitumor Pyruvate Glucose CPI-613 Lactate Significance: This study proposes targeted metabolic reprogramming as a valid combinatorial strategy to enhance the translational efficacy of oncolytic virus-based cancer therapies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Therefore, metabolic reprogramming is a promising approach to increase the therapeutic potential of reovirus in cancer patients [163]. Another interesting study found that pre-conditioning tumours with bevacizumab-a vascular endothelial growth factor (VEGF) inhibitor-and then withdrawing treatment, rendered endothelial cells susceptible to reovirus infection, induced vascular collapse and promoted immune-mediated tumour clearance [164].…”
Section: Unlocking the Potential Of Reovirus With Combination Therapeuticsmentioning
confidence: 99%
“…Therefore, metabolic reprogramming is a promising approach to increase the therapeutic potential of reovirus in cancer patients [163]. Another interesting study found that pre-conditioning tumours with bevacizumab-a vascular endothelial growth factor (VEGF) inhibitor-and then withdrawing treatment, rendered endothelial cells susceptible to reovirus infection, induced vascular collapse and promoted immune-mediated tumour clearance [164].…”
Section: Unlocking the Potential Of Reovirus With Combination Therapeuticsmentioning
confidence: 99%
“…A recent study showed that using 2-deoxyglucose (2DG) to block glycolysis or through restricting glucose amount will enhance oncolytic adenoviruses activity in permissive and poorly permissive cancer cells [28]. Furthermore, pyruvate dehydrogenase kinase inhibition showed to improve reovirus oncolytic anti-tumor efficacy in several cancer types [29]. We reported previously that 2DG would enhance oncolytic NDV against breast cancer cells through glycolysis inhibition by downregulation of glyceraldehyde3-phosphate (GAPDH) [30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increase in ceramide level has been implicated in the activation of the CD95 death receptor, induction of autophagy, and enhancement of cytotoxicity [23,24]. Knock down of ceramide synthase 6 suppressed autophagosome formation and cell death in breast cancer cells.…”
Section: Metabolites Associated With the Adenovirus-induced Autophagimentioning
confidence: 99%